"Those People Motivate and Inspire Me to Take My Treatment." Peer Support for Adolescents Living With HIV in Cape Town, South Africa. (10th March 2021) - Rencken, Camerin A.; Harrison, Abigail D.; Mtukushe, Bulelwa; Bergam, Scarlett; Pather, Ariana; Sher, Rebecca; Davidson, Bianca J.; Carrihill, Michelle; Matiwane, Mluleki; Kuo, Caroline; Galárraga, Omar; Hoare, Jacqueline
Adherence to antiretroviral therapy (ART) and psychosocial support to manage stigma and disclosure is essential for adolescents living with HIV (ALHIV). Peer support groups can help ALHIV and their families live successfully with HIV. This qualitative study aimed to examine adolescent and caregiver perspectives on peer support groups. Three themes emerged: (1) peer support encouraged adherence to ART, (2) serostatus disclosure outside the family was perceived as difficult, and (3) the peer support group fostered fundamental and meaningful peer relationships for ALHIV. Caregivers felt peer support groups increased self-acceptance and adherence for ALHIV across 3 domains: (1) as motivation for families and adolescents, (2) to increase adolescent independence and maturity, and (3) to help adolescents accept their HIV status and live successfully with HIV. These data highlight the importance of psychosocial support groups for ALHIV and caregivers, illustrating the benefits of a safe space with trusted relationships and open communication.